Adriaan van den Spiegel (1578–1625): Anatomist, physician, and botanist. Issue 7 (9th May 2014) - Ghosh, Sanjib Kumar; Sharma, Suranjali; Biswas, Sudipa; Chakraborty, Soumya
<x xml:space="preserve">Abstract</x> Adriaan van den Spiegel (1578–1625) was a Flemish anatomist and physician. He was one of the most prominent anatomists at the University of Padua during the 17th century and became professor of anatomy and surgery there in 1619. He was privileged to have two of the most accomplished anatomists of that period, Fabricius ab Aquapendente and Iulius Casserius, as his teachers. His anatomical works were published after his death by his pupil Bucretius and his son‐in‐law Liberalis Crema, with illustrations procured from Casserius's unpublished anatomical atlas. He contributed significantly to establishing basic morphological facts about the developing embryo in his text De formato foetu liber singularis. In his book De humani corporis fabrica libri decem, Spiegel's lobe (caudate lobe) of the liver and the linea semilunaris (Spiegel's line) on the lateral side of the rectus abdominis muscle were described for the first time. Subsequently, Spigelian aponeurosis (between the lateral margin of the rectus abdominis and the linea semilunaris) and Spigelian hernia (lateral ventral hernia) were named after him. He was a renowned physician in his time and was the first to give a detailed description of malaria. He made significant contributions as a botanist: the genus Spigelia, which has six species, is named after him. Clin. Anat. 27:952–957, 2014. © 2014 Wiley Periodicals, Inc.